2016
DOI: 10.3389/fnhum.2016.00014
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity within the Default Mode Network: Dynamic Causal Modeling of Resting-State fMRI Data

Abstract: The Default Mode Network (DMN) is a brain system that mediates internal modes of cognitive activity, showing higher neural activation when one is at rest. Nowadays, there is a lot of interest in assessing functional interactions between its key regions, but in the majority of studies only association of Blood-oxygen-level dependent (BOLD) activation patterns is measured, so it is impossible to identify causal influences. There are some studies of causal interactions (i.e., effective connectivity), however ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 48 publications
7
62
0
Order By: Relevance
“…When estimating a more complex model, one could be confident that the previous connectivity pattern does not change much and all changes in the extended model are associated with the new source (region of interest). In our previous work (Sharaev et al, 2016), we found a stable coupling pattern between the four basic DMN nodes. Here, we aimed at developing the model to assess its parameter stability when adding or removing active regions.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…When estimating a more complex model, one could be confident that the previous connectivity pattern does not change much and all changes in the extended model are associated with the new source (region of interest). In our previous work (Sharaev et al, 2016), we found a stable coupling pattern between the four basic DMN nodes. Here, we aimed at developing the model to assess its parameter stability when adding or removing active regions.…”
Section: Introductionmentioning
confidence: 63%
“…Regarding family a, one may recall from Figure 2 it is the full connected base, which was the best model when analyzing four source models (Sharaev et al, 2016). This means that no matter how the LHIP/RHIP region is included, the best connection pattern between these four nodes remains the same.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations